Public’s Understanding and Zakat Management on Agricultural Zakat - Nia Zulinda; Rahma Yulisa Kalbarini; Muhammad Mursalin (Department of Islamic Economics, Islamic University of Indonesia, 2022)
The purpose of this research is to find out and analyze the public's understanding of Agricultural Zakat and also the management in agricultural zakat in the Samata village, Tangaran, Sambas. The research type used in this research is field research. Data collection methods were done through observation, interviews and documentation, and relevant supporting literatures on the discussing issue. The data was further analyzed using a descriptive analysis method. The results showed that the community in that village had a general understanding of agricultural zakat. This could be seen from several indicators such as: how much the agricultural zakat nisab is, when they have to pay agricultural zakat, the amount that they have to pay and where they have to pay it, so that the village community whose harvests have reached the nisab always pay the zakat. The management in agricultural zakat in the village has two aspects, which are zakat’s collection and distribution. In terms of the management of agricultural zakat in Semata village, it can be said to be good. However, the non-centralization of the amil zakat institutions makes management overlap, because the zakat proceeds are not evenly distributed among the existing mosques. Keywords: Public understanding, zakat management, agricultural zakat